Layanan peminatan kegiatan ekstrakurikuler di SMP Negeri 17 Banda Aceh - Mariana Mariana; M. Husen; Said Nurdin (Program Studi Bimbingan dan Konseling, FKIP Universitas Syiah Kuala, 2017)
This study aims to determine the implementation of specialization services on extracurricular activities in SMP Negeri 17 Banda Aceh. This research used desciptive qualitative approach. The subjects of this study were guidance teachers, OSIS supervisors, teachers, deputy principal of student affairs and each student representative who participated in extracurricular activities. The object of research was the implementation of specialization services on extracurricular activities. Data collection used was observation and interview. The results of the study indicate that the specialization of school service activities are data collection, specialization information, identification and determination of specialization, adjustment and monitoring / follow up. Data collection of students viewed from the achievements of students, the value of the UN seen from the highest score on each subject listed on student report cards, ideals and parental support. Furthermore, the BK teacher provides special information about extracurricular activities and secondary school. Step identification and determination of student interest has been done by teachers BK yet not maximal for the lack of special tools in the identification and determination of interest, the way that has been used only by conducting interviews. The types of extracurricular activities include mandatory extracurricular activities such as scouts, and selected activities that are of interest to students such as volleyball, soccer, art galleries, drum bands, Olympics and the Youth Red Cross (PMR). Obstacles found in the implementation of extracurricular activities that lack of facilities and infrastructure, school funds and lack of supervisors of each extracurricular activity. Keywords: service specialization, extracurricular activities ABSTRAKPenelitian ini bertujuan untuk mengetahui implementasi layanan peminatan terhadap kegiatan ekstrakurikuler di SMP Negeri 17 Banda Aceh. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Subjek penelitian ini adalah guru BK, pembina Osis, guru bidang studi, wakil kesiswaan dan masing-masing perwakilan siswa yang mengikuti kegiatan ekstrakurikuler. Sedangkan objek penelitian adalah implementasi layanan peminatan terhadap kegiatan ekstrakurikuler. Pengumpulan data menggunakan observasi dan wawancara. Hasil penelitian menunjukkan bahwa langkah-langkah layanan peminatan yang dilakukan yaitu pengumpulan data, informasi peminatan, identifikasi dan penetapan peminatan, penyesuaian dan monitoring/tindak lanjut. Pengumpulan data siswa dilihat dari prestasi yang pernah diraih siswa, nilai UN yang dilihat dari nilai tertinggi pada setiap mata pelajaran yang tercantum pada raport siswa, cita-cita dan dukungan orang tua. Selanjutnya guru BK memberikan informasi peminatan tentang kegiatan ekstrakurikuler dan sekolah lanjutan. Langkah identifikasi dan penetapan minat siswa sudah dilakukan oleh guru BK namun belum maksimal karena tidak adanya alat khusus dalam identifikasi dan penetapan minat, cara yang selama ini dipakai hanya dengan melakukan wawancara. Adapun jenis-jenis kegiatan ekstrakurikuler antara lain kegiatan ekstrakurikuler wajib yaitu pramuka, dan kegiatan pilihan yang menjadi minat siswa seperti bola voli, sepak bola, sanggar seni, drum band, olimpiade, dan PMR (Palang merah remaja). Kendala yang ditemukan pada pelaksanaan kegiatan ekstrakurikuler yaitu kurangnya sarana dan prasarana, dana sekolah dan kurangnya tenaga pembimbing masing-masing kegiatan ekstrakurikuler.Kata kunci: layanan peminatan, Kegiatan ekstrakurikuler